Strategies for overcoming challenges in selective electrochemical CO2 conversion to ethanol - Wang, Zihong; Li, Yecheng; Ma, Zhihao; Wang, Dazhuang; Ren, Xiaodi (iScience, 2024)
The electrochemical conversion of carbon dioxide (CO2) to valuable chemicals is gaining significant attention as a pragmatic solution for achieving carbon neutrality and storing renewable energy in a usable form. Recent research increasingly focuses on designing electrocatalysts that specifically convert CO2 into ethanol, a desirable product due to its high-energy density, ease of storage, and portability. However, achieving high-efficiency ethanol production remains a challenge compared to ethylene (a competing product with a similar electron configuration). Existing electrocatalytic systems often suffer from limitations such as low energy efficiency, poor stability, and inadequate selectivity toward ethanol. Inspired by recent progress in the field, this review explores fundamental principles and material advancements in CO2 electroreduction, emphasizing strategies for ethanol production over ethylene. We discuss electrocatalyst design, reaction mechanisms, challenges, and future research directions. These advancements aim to bridge the gap between current research and industrialized applications of this technology. [Display omitted] Chemical engineering; Chemistry; Electrochemical engineering; Electrochemistry.